2018
DOI: 10.1002/syn.22031
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid binding protein deletion prevents stress‐induced preference for cocaine and dampens stress‐induced corticosterone levels

Abstract: Genetic and pharmacological manipulation of endocannabinoid (eCB) signaling has previously been shown to have an important role on the rewarding properties of drugs of abuse, including cocaine. Recently, fatty acid binding proteins (FABPs) have been proposed as intracellular transporters of the endocannabinoid anandamide (AEA) as well as other bioactive lipids to their catabolic enzyme, fatty acid amide hydrolase (FAAH). The role of these transporters in modulating the brains reward system has yet to be invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Fabp7 was the most highly upregulated DEG in Npas2 mutants across all regions. It regulates fatty acid uptake in astrocytes, sleep (Gerstner et al, 2017) and drug seeking under stressful conditions (Hamilton et al, 2018). Fabp7 is rhythmically expressed throughout the brain (Schnell et al, 2014) and is similarly upregulated in Arntl and Nr1d1 knock-out mice (Schnell et al, 2014;Gerstner and Paschos, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Fabp7 was the most highly upregulated DEG in Npas2 mutants across all regions. It regulates fatty acid uptake in astrocytes, sleep (Gerstner et al, 2017) and drug seeking under stressful conditions (Hamilton et al, 2018). Fabp7 is rhythmically expressed throughout the brain (Schnell et al, 2014) and is similarly upregulated in Arntl and Nr1d1 knock-out mice (Schnell et al, 2014;Gerstner and Paschos, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment with the FABP inhibitor SBFI26 significantly reduced ethanol consumption in mice as FABP5 and FABP7 inhibited the transport of anandamide to fatty acid amide hydrolase and elevated anandamide levels in the mouse brain, thereby increasing the preference and consumption of ethanol [ 163 ]. FABP 5/7 double knockout mice exhibit similar acquisition of cocaine-induced CPP relative to WT mice, whereas these mice do not exhibit stress-induced preference and show decreased levels of serum corticosterone under stress relative to WT mice [ 164 ]. Recent studies have reported that FABP5 knockdown in the adult rat NAc shell with RNA interference via adeno-associated viral vector attenuates cocaine self-administration and modulates the excitability of MSNs in the NAc shell [ 165 ].…”
Section: Involvement Of Lcpufas and The Novel Target Fabp3 In Nicomentioning
confidence: 99%
“… Rorick-Kehn et al, 2016 eCB (anandamide) enhancer URB597, Cannabidiol + + ? Gonzalez-Cuevas et al, 2018 Chauvet et al, 2014 ; Hamilton et al, 2018 ; Gonzalez-Cuevas et al, 2018 5-HT-3 antagonist Ondansetron, tropisetron + ? ?…”
Section: Neuropharmacological Targetsmentioning
confidence: 99%
“…Using this approach, they demonstrated that URB597 significantly attenuated YOH-reinstatement of cocaine seeking ( Chauvet et al, 2014 ). Targeting fatty acid binding proteins, which transport AEA intracellularly to FAAH for degradation, is a related strategy to interfere with stress-induced drug seeking ( Hamilton et al, 2018 ).…”
Section: Neuropharmacological Targetsmentioning
confidence: 99%